Anti-radiation boron-containing cement for nuclear power and preparation method thereof

By adjusting the proportion of components such as silicate cement, boron nitride, fine river sand and modified fly ash in radiation-resistant boron-containing cement for nuclear power, the problem of hindered cement hydration reaction is solved, significantly improving the compressive strength and durability of the cement, and enhancing its neutron radiation resistance.

CN119874299AActive Publication Date: 2025-04-25SHANDONG BEICHEN MECHANICAL & ELECTRICAL EQUIP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510173020.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-25
Estimated Expiration
2045-02-17

AI Technical Summary

Technical Problem

During the hardening process of existing radiation-resistant boron-containing cement for nuclear power, the calcium borate hydrated film formed by the reaction of boron elements with calcium ions in the cement prevents the contact between cement particles and external solutions, resulting in the cement hydration reaction that cannot proceed normally, thereby affecting the strength development of cement.

Method used

By using specific raw material combinations, including silicate cement, boron nitride, fine river sand and modified fly ash, the proportion of each component is adjusted to promote the cement hydration reaction, improve the compactness and cohesion of the cement, thereby improving its compressive strength and durability.

Benefits of technology

It significantly improves the compressive strength and durability of radiation-resistant boron-containing cement for nuclear power, improves the strength development of cement, and enhances its shielding effect on neutron radiation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005274594630000091
    Figure BDA0005274594630000091
  • Figure BDA0005274594630000101
    Figure BDA0005274594630000101
Patent Text Reader

Abstract

The invention belongs to the technical field of building materials, and particularly discloses anti-radiation boron-containing cement for nuclear power and a preparation method of the anti-radiation boron-containing cement. The anti-radiation boron-containing cement for nuclear power is prepared from the following raw materials in parts by weight: 325 to 342 parts of Portland cement, 115 to 128 parts of boron nitride, 650 to 662 parts of fine river sand and 226 to 238 parts of water. The prepared anti-radiation boron-containing cement for nuclear power has good strength and tensile strength, a certain amount of Portland cement, boron nitride and fine river sand are arranged, and the compressive strength and durability of the anti-radiation boron-containing cement for nuclear power can be remarkably improved through cooperation of all the components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building materials, and in particular to a radiation-proof boron-containing cement for nuclear power and a preparation method thereof. Background Art

[0002] Radiation-proof boron cement for nuclear power is a special building material. It is a kind of cement made by grinding high-alumina cement clinker, calcined boron magnesium stone and natural anhydrite. Due to its excellent radiation-proof performance, it is widely used in radiation places such as nuclear power plants, radioactive medical equipment rooms, and biochemical laboratories.

[0003] With the development of nuclear power plant construction and the increase in the demand for radioactive waste treatment, the demand for radiation protection materials is also growing. Boron is widely used in radiation protection materials due to its good absorption performance for neutrons. The BO3 ions in the boron element have a large cross-sectional area for neutrons. When neutrons pass through the boron element, they will be absorbed and stimulate various ions and gamma rays such as α, Li, Be, etc., thereby slowing down the speed and energy of radiation and reducing the radiation dose.

[0004] During the hardening process of the existing radiation-proof boron-containing cement for nuclear power, the boron element reacts with the calcium ions in the cement to form a dense calcium borate hydrate film that covers the surface of the cement particles, preventing the cement particles from contacting the external solution, resulting in the cement hydration reaction being unable to proceed normally, thereby affecting the strength development of the cement. Summary of the invention

[0005] In order to improve the problem of poor strength of radiation-proof boron-containing cement for nuclear power, the present application provides a radiation-proof boron-containing cement for nuclear power and a preparation method thereof.

[0006] The present application provides a radiation-proof boron-containing cement for nuclear power, which adopts the following technical solution: A radiation-proof boron-containing cement for nuclear power comprises the following raw materials, measured by weight: 325-342 parts of silicate cement, 115-128 parts of boron nitride, 650-662 parts of fine river sand and 226-238 parts of water.

[0007] By adopting the above technical solution, silicate cement is the main component of cement, providing the basic strength and hardening performance of the mixture, limiting the amount of silicate cement, and ensuring that the cement mixture has sufficient structural strength. Boron nitride has good thermal and chemical stability, and also has strong neutron absorption ability, which improves the radiation protection performance of cement. Fine river sand has a small particle size and a large surface area, which can fully fill the gaps between cement particles and improve the density and cohesion of cement.

[0008] The hydrated calcium borate film formed by the reaction of boron and calcium ions in cement has a complex effect on the development of cement strength, while fine river sand helps promote cement hydration reaction and improve cement strength. After mixing with cement, fine river sand can provide a better reaction interface and promote cement hydration reaction. The cementitious substances produced by cement hydration can better fill the gaps between fine river sand particles and form a more compact structure.

[0009] Fine river sand and cement hydration products together constitute the skeleton structure of cement, which directly contributes to the strength of cement. Setting a certain amount of silicate cement, boron nitride, and fine river sand, the combination of each component can significantly improve the compressive strength and durability of radiation-proof boron-containing cement for nuclear power.

[0010] Preferably, in parts by weight, there are 333 parts of silicate cement, 122 parts of boron nitride, 656 parts of fine river sand, and 231 parts of water.

[0011] By adopting the above technical scheme, the dosage points between silicate cement, boron nitride and fine river sand are further limited. In the radiation-proof boron-containing cement for nuclear power, silicate cement, as a basic cementitious material, can form a dense structure with other components. Boron nitride has excellent neutron radiation protection performance due to its physicochemical properties of wide band gap and high thermal conductivity. Adding boron nitride to radiation-proof boron-containing cement for nuclear power can significantly improve the neutron radiation protection ability of cement. Fine river sand can fill the gaps between silicate cement particles, improve the density and cohesion of cement, and the hydrated calcium borate film formed by the reaction of boron elements with calcium ions in cement affects the strength of cement, while fine river sand and silicate cement hydration products together constitute the skeleton structure of cement, promote the hydration reaction of cement, and improve the strength of cement system. The combination of various components in the radiation-proof boron-containing cement for nuclear power further improves the compressive strength and durability of cement.

[0012] Preferably, it also includes 50-60 parts of modified fly ash, 20-30 parts of gypsum, and 40-45 parts of modified attapulgite.

[0013] By adopting the above technical solution, the modified fly ash can fill the voids in the cement cementitious system, increase the density of the cement, and thus improve its strength; at the same time, the silicates and aluminates in the fly ash will react with other components in the cement to generate new cementing substances, further enhancing the mechanical properties and durability of the cement. Gypsum adjusts the setting time of cement to prevent the cement from setting too quickly, and cooperates with the modified fly ash to improve the mechanical strength of the cement. The modified attapulgite has porosity and good adsorption, which can increase the internal space of the cement, reduce the porosity, increase the hardness of the cement, and make the quality more stable and durable; moreover, the porous structure and strong adsorption of attapulgite can adsorb and fix radioactive substances, reducing their radiation impact on the surrounding environment.

[0014] Preferably, the method for preparing the modified fly ash comprises the following steps: (1) dispersing fly ash in a salicylic acid solution, stirring for 20-25 minutes, washing with water, and then dispersing in a potassium hydroxide solution, stirring for 35-40 minutes, washing with water, and calcining at 340-350° C. for 30-35 minutes to obtain pretreated fly ash; (2) dispersing the modified blast furnace slag in deionized water, adding the pretreated fly ash, polyvinyl alcohol and silane coupling agent of step (1), stirring at a temperature of 60-65° C. for 2-3 hours, filtering, and obtaining a mixture; (3) spraying nano glue on the surface of the mixture in step (2), drying, grinding, and obtaining modified fly ash; Disperse nano silicon dioxide in deionized water, add polyvinyl alcohol and sodium dodecyl sulfate, stir evenly, and obtain nano glue.

[0015] By adopting the above technical scheme, the surface of fly ash is treated with salicylic acid to improve the wettability and dispersibility of the fly ash surface, and then the surface of fly ash is further treated with potassium hydroxide solution to remove other impurities in the fly ash. The obtained pretreated fly ash has good structural stability and dispersibility, which is conducive to subsequent mixing with other components.

[0016] Both modified blast furnace slag and fly ash are highly active. Modified blast furnace slag can be loaded on the particle surface and pores of fly ash to increase the strength and stability of fly ash. The active components in blast furnace slag and fly ash can subsequently react chemically with the hydration products in cement clinker to generate new compounds with high strength, thereby enhancing the strength of cement. Polyvinyl alcohol has good solubility and stability. As a binder, it makes the modified blast furnace slag and fly ash adhere tightly, increases the performance stability of the modified fly ash, and makes the modified fly ash have better strength. Silane coupling agent acts as a bridge to connect blast furnace slag, fly ash and polyvinyl alcohol, enhances the interfacial bonding between them, and helps to improve the overall strength and durability of the material.

[0017] Nano glue is evenly sprayed onto the mixture surface obtained in step (2), and the nano glue is composed of nano silicon dioxide, polyvinyl alcohol, glutaraldehyde and sodium dodecyl sulfate, which is used to enhance the cohesive force and stability of the mixture, further making the modified blast furnace slag and fly ash bonded tightly, increasing the performance stability of the modified fly ash, and subsequently improving the mechanical strength and durability of the cement. In the nano glue, nano silicon dioxide provides excellent mechanical properties and stability, polyvinyl alcohol increases the viscosity of the nano glue, making it more adhesive, and sodium dodecyl sulfate can reduce the surface energy of nano silicon dioxide particles by electrostatic adsorption and solvation, so that it is evenly dispersed in the mixed system of anhydrous ethanol and polyvinyl alcohol, and the nano glue obtained has good viscosity and mechanical strength, which helps to make other components bonded tightly in the subsequent process, and improves the comprehensive performance of the modified fly ash.

[0018] Preferably, the mass ratio of the fly ash, modified blast furnace slag and nano glue is 1:0.6-0.7:0.2-0.3.

[0019] By adopting the above technical scheme, the mass ratio of fly ash, modified blast furnace slag and nano glue is further limited within a certain range, and the obtained modified fly ash has better comprehensive performance. The modified blast furnace slag has a dense structure and a strong mechanical structure, and can be loaded on the surface and pores of the fly ash to improve the structural strength of the fly ash. The nano glue has excellent adhesion and film-forming properties, and can coat the fly ash, so that the fly ash and modified blast furnace slag are tightly bonded, thereby increasing the mechanical properties and durability of the modified fly ash, and subsequently improving the compressive strength, flexural strength and impermeability of the cement, further optimizing the radiation protection performance of the radiation-proof boron-containing cement for nuclear power, so that it has a better shielding effect against radiation such as X-rays, gamma rays, fast neutrons and thermal neutrons.

[0020] Preferably, the preparation method of the modified blast furnace slag comprises the following steps: washing the blast furnace slag with water to remove impurities, then dispersing it in a sulfuric acid solution, ultrasonically dispersing it for 3-4 hours, filtering, washing it with water, and then dispersing it in a sodium hydroxide solution, ultrasonically dispersing it for 1-2 hours, and washing it with water to obtain pretreated blast furnace slag; dispersing the pretreated blast furnace slag in deionized water, adding glass fiber, hydroxypropyl methylcellulose and sodium gluconate, stirring it for 4-6 hours, and drying it to obtain modified blast furnace slag.

[0021] By adopting the above technical scheme, sulfuric acid reacts chemically with certain components in blast furnace slag to remove impurities and change the surface properties of blast furnace slag. Sodium hydroxide solution further treats the blast furnace slag to improve the pH value and surface properties of the blast furnace slag and increase the specific surface area of ​​the blast furnace slag, so that the blast furnace slag is conducive to mixing with subsequent components.

[0022] The blast furnace slag after pretreatment is dispersed in deionized water, and glass fiber, hydroxypropyl methylcellulose and sodium gluconate are added. The glass fiber has good strength and toughness, can be adsorbed on the surface and pores of the blast furnace slag, and increases the strength and toughness of the blast furnace slag. Hydroxypropyl methylcellulose has excellent bonding properties, can improve the bonding force between blast furnace slag particles, makes the blast furnace slag particles and the glass fiber better bonded, and increases the structural strength and mechanical properties of blast furnace slag particles. Sodium gluconate has good dispersibility, helps the dispersion of blast furnace slag particles and glass fiber in deionized water, and avoids the reunion between particles. The modified blast furnace slag obtained has excellent physical and chemical properties, such as high strength, high toughness, good bonding and dispersibility, and is subsequently applied to fly ash to improve the corresponding properties of fly ash.

[0023] Preferably, the method for preparing the modified attapulgite comprises the following steps: (1) dispersing attapulgite in a hydrochloric acid solution, washing with water, calcining at 300-320° C. for 2-3 hours, and then dispersing in deionized water, adding betaine, filtering, and drying to obtain treated attapulgite; (2) Dispersing the modified wood chips in deionized water, adding the treated attapulgite of step (1), stirring at a temperature of 65-70° C. for 1-2 h, adding sodium alginate and barium sulfate, continuing to stir for 1-2 h, and drying to obtain modified attapulgite.

[0024] By adopting the above technical scheme, attapulgite is dispersed in a hydrochloric acid solution, and the hydrochloric acid can react with impurities or certain components on the surface of the attapulgite, thereby removing these impurities or changing the surface properties of the attapulgite; calcining at 300-320°C further removes volatiles and organic matter in the attapulgite, while improving its thermal stability and mechanical strength.

[0025] Betaine improves the dispersibility of attapulgite in water and reacts with the hydroxyl and carboxyl functional groups on its surface, changing the surface properties and types of functional groups of attapulgite, improving the dispersibility of attapulgite in water, thereby improving its dispersion stability and facilitating subsequent mixing with other components.

[0026] The modified sawdust has a porous structure and good thermal insulation performance. It can be adsorbed on the surface of attapulgite to increase the fluidity, strength and thermal insulation performance of attapulgite. Sodium alginate has good adhesion and film-forming properties, which makes attapulgite and modified sawdust adhere tightly, making the modified attapulgite have excellent comprehensive performance. Barium sulfate can be filled in the pores of modified sawdust and attapulgite, increasing the density and hardness of modified attapulgite and improving the radiation protection performance of subsequent cement.

[0027] Preferably, the mass ratio of the attapulgite, the modified wood chips and the sodium alginate is 1:0.4-0.5:0.15-0.25.

[0028] By adopting the above technical scheme, the mass ratio of attapulgite, modified sawdust and sodium alginate is further limited within a certain range, and the obtained attapulgite has excellent mechanical strength and durability. The attapulgite has excellent adsorption performance and ion exchange capacity, and reacts with cement to generate new hydration products, fill the pores, and improve the density and strength of the material. The modified sawdust has a porous structure and can be adsorbed on the surface of attapulgite to increase the thermal insulation performance of attapulgite. Sodium alginate has good stability and viscosity, and promotes the bonding of attapulgite and modified sawdust. In the radiation-proof boron-containing cement for nuclear power, it can play multiple roles such as enhancing radiation protection performance, improving material strength, improving thermal insulation performance, enhancing material stability, improving impermeability, and promoting the solidification of radioactive substances.

[0029] Preferably, the preparation method of the modified sawdust comprises the following steps: grinding the sawdust, dispersing it in ammonia water, stirring for 10-15 minutes, washing with water, and then dispersing it in deionized water, adding silicon carbide whiskers, starch, and sodium hexametaphosphate, stirring at 70-75° C. for 2-3 hours, and drying to obtain modified sawdust.

[0030] By adopting the above technical solution, ammonia water activates the surface of sawdust to improve the dispersibility and stability of sawdust, and then disperses it in deionized water, and adds silicon carbide whiskers, starch, and sodium hexametaphosphate. Silicon carbide whiskers have high strength and high elastic modulus, and can be loaded in the structure and pores of sawdust to increase the mechanical properties and wear resistance of sawdust. Starch has good dispersibility, hygroscopicity and adhesion, which helps the adhesion between sawdust and silicon carbide whiskers and increases the performance stability of sawdust. Sodium hexametaphosphate helps to maintain the dispersibility of sawdust particles, so that silicon carbide whiskers can be evenly loaded on the surface of sawdust. The modified sawdust has excellent dispersibility, mechanical properties and wear resistance, which in turn helps to modify the corresponding properties of attapulgite.

[0031] In the second aspect, the present application also provides a method for preparing radiation-proof boron-containing cement for nuclear power, comprising the following steps: mixing silicate cement, boron nitride, fine river sand and water, stirring evenly, and grinding until the residue passing through a 40μm square hole sieve is no more than 10%, to obtain radiation-proof boron-containing cement for nuclear power.

[0032] By adopting the above technical scheme and the above preparation method, the operation is simple and the process time is short, which helps to improve the production efficiency of preparing radiation-proof boron-containing cement for nuclear power. The obtained radiation-proof boron-containing cement for nuclear power has good mechanical properties.

[0033] In summary, this application has the following beneficial effects: 1. In the present application, the calcium borate hydrate film formed by the reaction of boron element with calcium ions in cement has a complex effect on the development of cement strength, while fine river sand helps to promote cement hydration reaction and improve cement strength. After mixing with cement, fine river sand can provide a better reaction interface, promote cement hydration reaction, and improve cement density and cohesion.

[0034] 2. The modified fly ash in this application can fill the voids in the cement cementitious system, increase the density of cement, and thus improve its strength; at the same time, the silicates and aluminates in the fly ash will react with other components in cement to generate new cementitious substances, further enhancing the mechanical properties and durability of cement.

[0035] 3. The modified attapulgite in this application has porosity and good adsorption properties, which can increase the internal space of cement, reduce porosity, increase the hardness of cement, and make the quality more stable and durable; moreover, the porous structure and strong adsorption properties of attapulgite can adsorb and fix radioactive substances and reduce their radiation impact on the surrounding environment. DETAILED DESCRIPTION

[0036] The present application is further described in detail below with reference to the embodiments.

[0037] The raw materials used in the examples and comparative examples can all be obtained commercially.

[0038] Preparation example of modified fly ash Preparation Example 1-1 The preparation method of modified fly ash comprises the following steps: (1) 80 kg of fly ash was dispersed in 100 L of 8% salicylic acid solution, stirred for 25 min, washed with water, and then dispersed in 110 L of 12% potassium hydroxide solution, stirred for 38 min, washed with water, and calcined at 345° C. for 35 min to obtain pretreated fly ash; (2) dispersing the modified blast furnace slag in 90 L of deionized water, adding the pretreated fly ash of step (1), 7 kg of polyvinyl alcohol and 3 kg of silane coupling agent KH-550, stirring at a temperature of 65° C. for 3 h, filtering, and obtaining a mixture; (3) spraying nano glue on the surface of the mixture in step (2), drying, grinding, and obtaining modified fly ash; 8 kg of nano-silicon dioxide was dispersed in 30 L of deionized water, 6 kg of polyvinyl alcohol and 3 kg of sodium dodecyl sulfate were added, and the mixture was stirred evenly to obtain nano-glue, and the required amount was selected to prepare modified fly ash.

[0039] The mass ratio of fly ash, modified blast furnace slag and nano glue is 1:0.6:0.3.

[0040] The preparation method of modified blast furnace slag comprises the following steps: washing 70 kg of blast furnace slag with water to remove impurities, dispersing it in 100 L of sulfuric acid solution with a mass fraction of 5%, ultrasonically dispersing it for 4 hours, filtering, washing it with water, dispersing it in 100 L of sodium hydroxide solution with a mass fraction of 10%, ultrasonically dispersing it for 2 hours, washing it with water, and obtaining pretreated blast furnace slag; dispersing the pretreated blast furnace slag in 150 L of deionized water, adding 18 kg of glass fiber, 14 kg of hydroxypropyl methylcellulose and 6 kg of sodium gluconate, stirring it for 6 hours, and drying it to obtain modified blast furnace slag.

[0041] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), no modified blast furnace slag is added.

[0042] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (3), no nano glue is added.

[0043] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of fly ash, modified blast furnace slag and nano glue is 1:0.7:0.2.

[0044] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of fly ash, modified blast furnace slag and nano glue is 1:0.1:0.6.

[0045] Preparation Example 1-6 The difference from Preparation Example 1-1 is that no glass fiber is added in the preparation method of modified blast furnace slag.

[0046] Preparation Example 1-7 The difference from Preparation Example 1-1 is that hydroxypropyl methylcellulose is not added in the preparation method of modified blast furnace slag.

[0047] Preparation example of modified attapulgite Preparation Example 2-1 The preparation method of modified attapulgite comprises the following steps: (1) dispersing 60 kg of attapulgite in 85 L of 5% hydrochloric acid solution, washing with water, calcining at 320° C. for 3 h, and then dispersing in 90 L of deionized water, adding 5 kg of betaine, filtering, and drying to obtain treated attapulgite; (2) Dispersing the modified wood chips in 180 L of deionized water, adding the treated attapulgite of step (1), stirring at 70° C. for 2 h, adding sodium alginate and 4 kg of barium sulfate, continuing stirring for 2 h, and drying to obtain modified attapulgite.

[0048] The mass ratio of attapulgite, modified sawdust and sodium alginate is 1:0.4:0.15.

[0049] The preparation method of modified sawdust comprises the following steps: grinding 45 kg of sawdust, dispersing in 60 L of 18% ammonia water by mass, stirring for 15 min, washing with water, and then dispersing in 67 L of deionized water, adding 12 kg of silicon carbide whiskers, 9 kg of starch, and 3 kg of sodium hexametaphosphate, stirring at 75° C. for 3 h, and drying to obtain modified sawdust.

[0050] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no modified wood chips are added.

[0051] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (2), no sodium alginate is added.

[0052] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of attapulgite, modified wood chips and sodium alginate is 1:0.5:0.25.

[0053] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of attapulgite, modified wood chips and sodium alginate is 1:0.1:0.6.

[0054] Preparation Example 2-6 The difference from Preparation Example 2-1 is that silicon carbide whiskers are not added in the preparation method of the modified wood chips.

[0055] Preparation Example 2-7 The difference from Preparation Example 2-1 is that starch is not added in the preparation method of the modified wood chips. Example

[0056] Example 1 A radiation-proof boron-containing cement for nuclear power, comprising the following raw materials by weight: 333 kg of silicate cement, 122 kg of boron nitride, 656 kg of fine river sand, and 231 kg of water; Among them, the silicate cement uses silicate cement coded as P·I, and its quality meets the requirements of GB175-2017.

[0057] The fine river sand is screened fine river sand with a fineness modulus μf of 1.9 and a dryness of ≤1%. The quality meets the requirements of JGJ52-2006.

[0058] Boron nitride with a purity of BN ≥ 98% is used, which complies with standard 1108AT0041.

[0059] Use tap water with a chloride ion content of less than 30 mg / L and quality that meets the requirements of JGJ63-2006.

[0060] The preparation method of the above-mentioned radiation-proof boron-containing cement for nuclear power comprises the following steps: mixing silicate cement, boron nitride, fine river sand and water, stirring evenly, and grinding until the residue passing through a 40μm square hole sieve is 8%, thereby obtaining the radiation-proof boron-containing cement for nuclear power.

[0061] Example 2 A radiation-proof boron-containing cement for nuclear power, which differs from Example 1 in that it comprises the following raw materials by weight: 325 kg of silicate cement, 115 kg of boron nitride, 650 kg of fine river sand, and 226 kg of water.

[0062] Example 3 A radiation-proof boron-containing cement for nuclear power, which differs from Example 1 in that it contains 342 kg of silicate cement, 128 kg of boron nitride, 662 kg of fine river sand, and 238 kg of water.

[0063] Example 4 A radiation-proof boron-containing cement for nuclear power, which differs from Example 1 in that it also includes 50 kg of modified fly ash, 20 kg of gypsum, and 40 kg of modified attapulgite.

[0064] The modified fly ash was prepared by using Preparation Example 1-1; and the modified attapulgite was prepared by using Preparation Example 2-1.

[0065] Example 5 A radiation-proof boron-containing cement for nuclear power, which differs from Example 1 in that it also includes 60 kg of modified fly ash, 30 kg of gypsum, and 45 kg of modified attapulgite.

[0066] Example 6 A radiation-proof boron-containing cement for nuclear power, which differs from Example 4 in that the modified fly ash is prepared using Preparation Example 1-2.

[0067] Example 7 A radiation-proof boron-containing cement for nuclear power, which differs from Example 4 in that the modified fly ash is prepared using Preparation Examples 1-3.

[0068] Example 8 A radiation-proof boron-containing cement for nuclear power, which differs from Example 4 in that the modified fly ash is prepared using Preparation Examples 1-4.

[0069] Example 9 A radiation-proof boron-containing cement for nuclear power, which differs from Example 4 in that the modified fly ash is prepared using Preparation Examples 1-5.

[0070] Example 10 A radiation-proof boron-containing cement for nuclear power, which differs from Example 4 in that the modified fly ash is prepared using Preparation Examples 1-6.

[0071] Embodiment 11 A radiation-proof boron-containing cement for nuclear power, which differs from Example 4 in that the modified fly ash is prepared using Preparation Examples 1-7.

[0072] Example 12 A radiation-proof boron-containing cement for nuclear power, which differs from Example 4 in that the modified attapulgite is prepared using Preparation Example 2-2.

[0073] Embodiment 13 A radiation-proof boron-containing cement for nuclear power, which differs from Example 4 in that the modified attapulgite is prepared using Preparation Example 2-3.

[0074] Embodiment 14 A radiation-proof boron-containing cement for nuclear power, which differs from Example 4 in that the modified attapulgite is prepared using Preparation Examples 2-4.

[0075] Embodiment 15 A radiation-proof boron-containing cement for nuclear power, which differs from Example 4 in that the modified attapulgite is prepared using Preparation Examples 2-5.

[0076] Example 16 A radiation-proof boron-containing cement for nuclear power, which differs from Example 4 in that the modified attapulgite is prepared using Preparation Examples 2-6.

[0077] Embodiment 17 A radiation-proof boron-containing cement for nuclear power, which differs from Example 4 in that the modified attapulgite is prepared using Preparation Examples 2-7.

[0078] Comparative Example Comparative Example 1 A radiation-proof boron-containing cement for nuclear power, which differs from Example 1 in that fine river sand is not added.

[0079] Performance testing The performance of the radiation-proof boron-containing cement for nuclear power prepared in Examples 1-17 and Comparative Example 1 was tested; Add a certain amount of water (water-cement ratio is 0.3) to the radiation-proof cement and stir it to make a slurry, then pour it into a hollow spherical mold shell with a thickness of 40 mm to form it. Put the mold into the curing room for curing for 24 hours, demould it, and then put the sample into a 20℃ water tank for curing for 28 days to obtain the radiation-proof cement test sample.

[0080] The compressive strength and flexural strength tests were conducted in accordance with the standard GB / T17671-1999 Cement mortar strength test method; the bonding strength test was conducted in accordance with the standard JGJ 110-2008 Building Engineering Facing Brick Bond Strength Test Standard. The impact test was carried out using the pendulum method and a XJJ-50 simply supported beam impact testing machine. The test results are shown in Table 1.

[0081] Table 1 Test data of embodiments and comparative examples It can be seen from Table 1 that the radiation-proof boron-containing cement for nuclear power prepared in Examples 1-3 of the present application has good mechanical properties, mechanical strength and radiation protection performance. Among them, the 3d compressive strength of Example 1 reaches 27.3MPa, the 28d compressive strength reaches 48.9MPa, the 3d flexural tensile strength is 5.1MPa, the 28d flexural tensile strength is 8.0MPa, the bonding strength is 1.42MPa, and the impact energy is 1296J / m 2 . The radiation protection performance was tested by a low-background multi-channel gamma spectrometer, and the radiation shielding rate of the tested embodiment 1 was 85.9%. However, fine river sand was not added to the comparative example 1. As can be seen from Table 1, compared with the embodiment 1, the test results of the 3d compressive strength, 28d compressive strength, 3d flexural tensile strength, 28d flexural tensile strength, bonding strength, and impact energy of the comparative example 1 were significantly worse than those of the embodiments 1-3, indicating that the prepared radiation-proof boron-containing cement for nuclear power has good mechanical properties and mechanical strength. The fine river sand and cement hydration products together constitute the skeleton structure of the cement, which improves the strength of the cement. A certain amount of silicate cement, boron nitride, fine river sand, and fine river sand are set, and the combination of each component can significantly improve the compressive strength and durability of the radiation-proof boron-containing cement for nuclear power.

[0082] The raw materials of Example 4-5 cement include modified fly ash, gypsum, and modified attapulgite. As can be seen from Table 1, the 3d compressive strength of Example 4 reaches 39.8MPa, the 28d compressive strength reaches 62.8MPa, the 3d flexural tensile strength is 8.3MPa, the 28d flexural tensile strength is 11.6MPa, the bonding strength is 2.35MPa, and the impact energy is 1534J / m 2 . It shows that modified fly ash can fill the voids in the cement cementitious system, increase the density of cement, and thus improve its strength; gypsum adjusts the setting time of cement to prevent cement from setting too quickly, and cooperates with modified fly ash to improve the mechanical strength of cement; modified attapulgite has porosity and good adsorption, which can increase the internal space of cement, reduce porosity, increase the hardness of cement, and make the quality more stable and durable.

[0083] The preparation methods of modified fly ash in Examples 6-7 do not add modified blast furnace slag and nano glue respectively, and the mass ratio of fly ash, modified blast furnace slag and nano glue is changed in Examples 8-9. It can be seen from Table 1 that the test results of 3d compressive strength, 28d compressive strength, 3d flexural tensile strength, 28d flexural tensile strength, bonding strength and impact energy of Examples 6-7 are significantly worse than those of Examples 4-5 and Example 8, while the test results of the corresponding properties of Example 9 are better than those of Examples 6-7, but worse than those of Examples 4-5 and Example 8, indicating that the modified blast furnace slag has a dense structure and a strong mechanical structure, can be loaded on the surface and pores of fly ash, and improves the structural strength of fly ash. Nano glue has excellent bonding and film-forming properties, can coat fly ash, so that fly ash and modified blast furnace slag are tightly bonded, the mechanical properties and durability of the modified fly ash are increased, and the compressive strength, flexural strength and impermeability of cement are subsequently improved.

[0084] The preparation methods of modified blast furnace slag in Examples 10-11 do not add glass fiber and hydroxypropyl methylcellulose respectively. It can be seen from Table 1 that the test results of 3d compressive strength, 28d compressive strength, 3d flexural tensile strength, 28d flexural tensile strength, bonding strength, and impact energy resistance of Examples 10-11 are significantly worse than those of Examples 4-5, but better than those of Example 6, indicating that the glass fiber has good strength and toughness, can be adsorbed on the surface and pores of blast furnace slag, and increase the strength and toughness of blast furnace slag; hydroxypropyl methylcellulose has excellent bonding properties, can improve the bonding force between blast furnace slag particles, make the blast furnace slag particles better bonded with the glass fiber, and increase the structural strength and mechanical properties of the blast furnace slag particles.

[0085] The preparation methods of modified attapulgite in Examples 12-13 do not add modified sawdust and sodium alginate respectively, and Examples 14-15 change the mass ratio of attapulgite, modified sawdust and sodium alginate. It can be seen from Table 1 that the test results of 3d compressive strength, 28d compressive strength, 3d flexural tensile strength, 28d flexural tensile strength, bonding strength and impact energy of Examples 12-13 are significantly worse than those of Examples 4-5 and Example 14, while the test results of the corresponding properties of Example 15 are better than those of Examples 12-13, but worse than those of Examples 4-5 and Example 14, indicating that the modified sawdust has a porous structure and can be adsorbed on the surface of attapulgite to increase the thermal insulation performance of attapulgite. Sodium alginate has good stability and viscosity, promotes the bonding of attapulgite and modified sawdust, and improves the material strength, enhances the material stability and improves the anti-permeability performance in radiation-proof boron cement for nuclear power.

[0086] The preparation methods of the modified sawdust of Examples 16-17 do not add silicon carbide whiskers and starch respectively. As can be seen from Table 1, the test results of 3d compressive strength, 28d compressive strength, 3d flexural tensile strength, 28d flexural tensile strength, bonding strength, and impact energy resistance of Examples 16-17 are significantly worse than those of Examples 4-5, but better than those of Example 12, indicating that silicon carbide whiskers have high strength and high elastic modulus, can be loaded in the structure and pores of sawdust, and increase the mechanical properties and wear resistance of sawdust; starch has good dispersibility, hygroscopicity and bonding properties, which facilitates the bonding between sawdust and silicon carbide whiskers and increases the performance stability of sawdust.

[0087] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A radiation-proof boron-containing cement for nuclear power, characterized in that: Calculated by weight, the raw materials include: 325-342 parts of silicate cement, 115-128 parts of boron nitride, 650-662 parts of fine river sand, and 226-238 parts of water.

2. The radiation-proof boron-containing cement for nuclear power according to claim 1, characterized in that: In terms of weight, there are 333 parts of Portland cement, 122 parts of boron nitride, 656 parts of fine river sand and 231 parts of water.

3. The radiation-proof boron-containing cement for nuclear power according to claim 1, characterized in that: The invention also comprises 50-60 parts of modified fly ash, 20-30 parts of gypsum and 40-45 parts of modified attapulgite.

4. The radiation-proof boron-containing cement for nuclear power according to claim 3, characterized in that: The preparation method of the modified fly ash comprises the following steps: (1) Dispersing fly ash in a salicylic acid solution, stirring for 20-25 minutes, washing with water, and then dispersing in a potassium hydroxide solution, stirring for 35-40 minutes, washing with water, and calcining at 340-350° C. for 30-35 minutes to obtain pretreated fly ash; (2) dispersing the modified blast furnace slag in deionized water, adding the pretreated fly ash, polyvinyl alcohol and silane coupling agent of step (1), stirring at a temperature of 60-65° C. for 2-3 hours, filtering, and obtaining a mixture; (3) spraying nano glue on the surface of the mixture in step (2), drying, grinding, and obtaining modified fly ash; Disperse nano silicon dioxide in deionized water, add polyvinyl alcohol and sodium dodecyl sulfate, stir evenly, and obtain nano glue.

5. The radiation-proof boron-containing cement for nuclear power according to claim 4, characterized in that: The mass ratio of the fly ash, modified blast furnace slag and nano glue is 1:0.6-0.7:0.2-0.

3.

6. The radiation-proof boron-containing cement for nuclear power according to claim 4, characterized in that: The preparation method of the modified blast furnace slag comprises the following steps: washing the blast furnace slag with water to remove impurities, dispersing it in a sulfuric acid solution, ultrasonically dispersing it for 3-4 hours, filtering it, washing it with water, dispersing it in a sodium hydroxide solution, ultrasonically dispersing it for 1-2 hours, and washing it with water to obtain pretreated blast furnace slag; The pretreated blast furnace slag is dispersed in deionized water, glass fiber, hydroxypropyl methylcellulose and sodium gluconate are added, stirred for 4-6 hours, and dried to obtain modified blast furnace slag.

7. The radiation-proof boron-containing cement for nuclear power according to claim 3, characterized in that: The preparation method of the modified attapulgite comprises the following steps: (1) dispersing attapulgite in a hydrochloric acid solution, washing with water, calcining at 300-320° C. for 2-3 hours, and then dispersing in deionized water, adding betaine, filtering, and drying to obtain treated attapulgite; (2) Dispersing the modified wood chips in deionized water, adding the treated attapulgite in step (1), stirring at a temperature of 65-70° C. for 1-2 h, adding sodium alginate and barium sulfate, continuing to stir for 1-2 h, and drying to obtain modified attapulgite.

8. The radiation-proof boron-containing cement for nuclear power according to claim 7, characterized in that: The mass ratio of the attapulgite, the modified wood chips and the sodium alginate is 1:0.4-0.5:0.15-0.

25.

9. The radiation-proof boron-containing cement for nuclear power according to claim 7, characterized in that: The preparation method of the modified sawdust comprises the following steps: grinding the sawdust, dispersing it in ammonia water, stirring it for 10-15 minutes, washing it with water, and then dispersing it in deionized water, adding silicon carbide whiskers, starch, and sodium hexametaphosphate, stirring it at 70-75° C. for 2-3 hours, and drying it to obtain the modified sawdust.

10. The method for preparing radiation-proof boron-containing cement for nuclear power according to claim 1, characterized in that: The method comprises the following steps: mixing silicate cement, boron nitride, fine river sand and water, stirring evenly, and grinding until the residue passing through a 40-mu m square hole sieve is no more than 10%, so as to obtain radiation-proof boron-containing cement for nuclear power.

Citation Information

Patent Citations

  • Neutron poison material and preparation method thereof, and nuclear critical safety storage tank

    CN114171215A

  • High-strength anti-crack concrete and preparation method thereof

    CN118479800A

  • Neutron shielding concrete

    JP5347075B1

  • Cement composition using cement admixtures for enhancing compressive strength

    KR1020130108222A

  • Method of preparing solidified and stabilized hazardous or radioactive liquids

    US5098612A